Effect of work environment and salary on private school teachers in Indonesia - HASANAH, E.; SUPARDI, S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to identify the effect of the work environment and salary on the level of job satisfaction of private school teachers in Indonesia. The number of participants in this study is 216 private school teachers in Yogyakarta, Indonesia. The results showed that the relationship between work environment and salary with the level of satisfaction of private school teachers in Indonesia could be seen from the regression equation: Y = 1,099 + 0,458 (X1) + 0,149 (X2) + e. The equation shows that salary contributes lower to job satisfaction compared to working environment conditions for private school teachers in Indonesia. RESUMEN Este estudio tiene como objetivo identificar el efecto del ambiente laboral y el salario en el nivel de satisfacción laboral de los maestros de escuelas privadas en Indonesia. El número de participantes en este estudio es de 216 maestros de escuelas privadas en Yogyakarta, Indonesia. Los resultados mostraron que la relación entre el ambiente de trabajo y el salario con el nivel de satisfacción de los maestros de escuelas privadas en Indonesia podría verse en la ecuación de regresión: Y = 1,099 + 0.458 (X1) + 0.149 (X2) + e. La ecuación muestra que el salario contribuye a una menor satisfacción laboral en comparación con las condiciones del entorno laboral para los maestros de escuelas privadas en Indonesia.